1999
DOI: 10.1038/sj.ejcn.1600694
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of vegetables and fruits among adults in five regions of Spain

Abstract: Objective: To assess the consumption of vegetables and fruits (V&F) in adults from ®ve regions in Spain according to sex, age and educational level. Design: Cross-sectional study within the members of the EPIC cohort in Spain. Setting: Three regions of the north of Spain (Asturias, Guipu Âzcoa and Navarra) and two regions of the south of Spain (Granada and Murcia). Subjects: 41 448 healthy volunteers (15 365 men, 25813 women), aged 29±69 y. Interventions: Information on habitual diet during the previous year w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Furthermore, in most countries the centres were selected bearing in mind the main purpose of the EPIC study: namely, the identification of cancer cases. Thus, although for some centres or countries it has been shown that our population has the same characteristics as populations with the same age -sex structure 14 , results shown here should not be considered as being representative at the country level.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in most countries the centres were selected bearing in mind the main purpose of the EPIC study: namely, the identification of cancer cases. Thus, although for some centres or countries it has been shown that our population has the same characteristics as populations with the same age -sex structure 14 , results shown here should not be considered as being representative at the country level.…”
Section: Discussionmentioning
confidence: 96%
“…Mean intake of total vegetables (excluding potatoes) and fruit was much lower in Ireland than in Spain 46 and Italy 47 but comparable to that in other countries. Intake of potatoes was similar to that in the UK 22 but higher than in other European countries for which data are reported 20,21,42 -47 .…”
Section: Contribution Of Vegetables and Fruit To Nutrientsmentioning
confidence: 91%
“…We have already reported on fruit and vegetable intake in Spain (Agudo et al, 1999), showing a high consumption of vegetables as a whole, although intake of cabbage and other foods of the genus Brassica was relatively low. The aim of this study is to assess the amount and types of cruciferous vegetables as well as the intake of glucosinolates in the adult Spanish population, and its relationship with some demographic and lifestyle factors.…”
Section: Introductionmentioning
confidence: 91%